A study on the role of interior design to safety and sanitary concerns in selected veterinary hospitals in Metro Manila - Olan, Nicole Alexis A.; Faustino, Johanna Victoria A. (Quezon City College of Home Economics, University of the Philippines Diliman, 2019)
This case study examined the role of interior design in creating a safe and clean environment in veterinary hospitals in Metro Manila. Due to their environment, injuries and diseases are common. Thus, the Epidemiological theory was used to study the relationship of interior design with the agent, host, and environment and determine interventions that would reduce their concerns. As a qualitative study, data was collected through observation of the waiting area and examination rooms of five veterinary hospitals, along with interviews with veterinarians and hospital staff. Interviews with two key informants were also executed and they were selected through purposive and snowball sampling. Instruments such as an observation and interview guide, camera, voice recorder, steel tape measure, and a PowerPoint presentation were used. the findings showed that functionality, efficiency, and disinfection are the prime considerations of the observed veterinary hospitals in their application of interior elements. Hence, only general specifications were implemented, where finishes, layout, and ventilation became an afterthought. However, these interior elements are important as it has direct relationship with the mentioned concerns, which may be linked to the growth of agents. Thus, endangering the environment and space users to become probable hosts. In conclusion, an interdisciplinary approach may be used to address all three factors and create a comprehensive hospital design with a safe and clean environment appropriate for quality care. Further research on the application of Epidemiological theory in interior environments, and the possible use of Evidence Based Design are recommended to gain more findings regarding the role of interior design in these establishments.
Thesis (B.S. Interior Design)--University of the Philippines Diliman
Keywords: Veterinary hospitals -- Sanitation -- Philippines -- Metro Manila; Veterinary hospitals -- Philippines -- Metro Manila -- Safety measures; Veterinary hospitals -- Environmental services -- Philippines -- Metro Manila; Interior decoration -- Philippines -- Metro Manila